A STUDY OF THE 1904 LITHOGRAPHIC EDITION OF MAWLUD-I SHARIF - Nizomjonova Zarina Nizomjon kizi (International Journal of Literature and Language Studies, 2026)
This article examines the bookmaking and calligraphic features of Xilvatiy’s Mawlud-i Sharif, published in 1904 in lithographic form. The study analyzes the decorative elements, writing style, page layout, as well as the sections Hajnoma and Tumornoma, highlighting their historical and cultural significance.